Use of Letermovir for Salvage Therapy for Resistant Cytomegalovirus in a Pediatric Hematopoietic Stem Cell Transplant Recipient. (31st July 2019) - Kilgore, Jacob T; Becken, Bradford; Varga, Matthew G; Parikh, Suhag; Prasad, Vinod; Lugo, Debra; Chang, Yeh-Chung
Abstract: We present here the first published use of letermovir for the treatment of resistant cytomegalovirus (CMV) in a pediatric patient. A 14-year-old girl underwent a double unrelated umbilical cord blood transplantation to treat her sickle cell disease (hemoglobin SS) and developed ganciclovir-resistant CMV DNAemia with end-organ involvement that was treated successfully with a combination of foscarnet and letermovir. After she was transitioned to letermovir monotherapy for secondary prophylaxis, she developed recurrent DNAemia with laboratory-confirmed ganciclovir, foscarnet, and letermovir resistance. Abstract : Pediatric data regarding the use of letermovir for prophylaxis and treatment in pediatric patients are lacking. If letermovir is used for salvage treatment purposes, combination therapy should be considered for patients at high risk.